CALCULATION OF INTERMEDIATE SUPPORTING PARTS OF INSEPARABLE PERFORATED BEAMS IN THE SOFTWARE COMPLEX «LIRA» (Collection of scientific works «Modern structures of metal and wood», 2021)
Due  to  the  simplicity  of  design  and  manufacture,  as  well  as  reliability  during operation,  beams  are  one  of  the  most  common  elements  used  in  industrial,  civil  and  public construction. The most rational cross-section of  metal beams are rolled  I-beams with inclined or parallel inner  faces of the shelves, the predominant use of which is due to the value of the  core distance, which is twice as much the same value for a rectangular section and almost three times for a round section. This figure is even higher for perforated profiles obtained from conventional rolling beams,  which  allow  you  to  compose  sections  with  increased  values  of  moments  of  inertia  and moments  of  resistance  without  increasing  material  consumptions.  For  inseparable  beams,  an additional  significant  factor  influencing  on  their  bearing  capacity,  is  the  structural  design  of  the intermediate support part. The aim of these researches is to study the stress-strain state of inseparable perforated beams of I-beam profile of different heights in areas near the intermediate support, the design of which is made without a transverse stiffening rib placed on the axis of the support, and with unwelded holes to the left and right of the support under the action of evenly distributed load in the software complex "Lira". The objectives of the study are to establish the actual values of stresses and strains in the characteristic cross sections of the inseparable perforated I-beam, which occur on the intermediate support, and perform a comparative analysis of numerical studies obtained in the software complex "Lira" for intermediate support node beams of different heights for actions of different magnitudes of loads. The analysis of the obtained diagrams of normal stresses was carried out, which showed that for the proposed design of the support part of the beam, the cross-sections with holes directly to the left and right of the support are calculated. The conclusion about necessity of carrying out further experimental-theoretical researches of various types of support parts of beams for the purpose of development  of  a  complex  technique  of  their  calculation  and  recommendations  on  definition  of rational scope of application of each of them is formulated.